Analisa Manajemen Dana Bank Syariah Dalam Konsep Pemasaran Konvensional - Wening Purbatin Palupi Soenjoto (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2018)
The development of banking is increasingly widespread to the corners of the village, people are beginning to understand about the more modern financial management. The conventional banking system that was first known to the public began to adapt the situation of religious issues such as the issue of sharia-based banking that began to be developed to enter the market niche of the Muslim community that promises profit and become a conventional bank marketing strategy by opening the opportunity of sharia bank as a sub-unit of marketing additionally that other conventional banks do not just as the ability to read the market but further expand the larger profits. Competition of conventional banks and sharia-based banks is getting stronger where the pattern of system of contracts and profit sharing strategies applied by sharia banking as a marketing strategy can be a major obstacle if not managed well and even become the main obstacle of sharia banking in doing competition with conventional banks.